Microneedle-coupled epidermal sensors for in-situ-multiplexed ion detection in interstitial fluids - Zhu, Dan Dan (2023)
Maintaining the concentrations of the various ions in the body fluids is critical to all living organisms. In this contribution, we designed a flexible microneedle patch coupled electrode array (MNP-EA) for the in situ multiplexed detection of ion species (Na+, K+, Ca2+, and H+) in tissue interstitial fluid (ISF). The microneedles (MNs) are mechanically robust for skin or cuticle penetration (0.21 N/needle) and highly swellable to quickly extract sufficient ISF onto the ion-selective electrochemical electrodes (~6.87 µL/needle in 5 minutes). The potentiometric sensor can simultaneously detect these ion species with nearly Nernstian response, in the ranges wider enough for diagnosis purposes (Na+: 0.75-200 mM, K+: 1-128 mM, Ca2+: 0.25-4.25 mM, pH: 5.5-8.5). The in vivo experiments on mice, human, and plants demonstrate the feasibility of MNP-EA for timely and convenient diagnosis of ion imbalances with minimal invasiveness. This transdermal sensing platform shall be instrumental to home-based diagnosis and health monitoring of chronic diseases, and is also promising for smart agriculture and study of plant biology.